PELATIHAN PEMBUATAN PUPUK ORGANIK ENCENG GONDOK (EICHORNIA CRASSIPES) DI DESA KESERANGAN, KECAMATAN PONTANG, KABUPATEN SERANG - Ubay Haki; Siti Nazdati Soleha; Syarifudin Syarifudin; Martina Dwi Rahayu (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Serangan Village, Pontang District, Serang Regency is a village where the majority of the population work as farmers, as rice-producing farmers. There are those who are concerned with managing agriculture, namely the farmer group in Keserangan Village which is in charge of rice cultivation, namely the Mekar Jaya Farmers Group. The main problem experienced by farmers in Keserangan Village is the lack of rice production which is caused by improper maintenance methods in terms of fertilizer application. This has caused rice yields for the last 1 year to fall short of expectations because they have decreased. The purpose of writing this Community Service article is to share knowledge about how to make water hyacinth organic fertilizer for rice farmers. The method used in this activity was in the form of training and mentoring in the practice of making organic water hyacinth fertilizer and its application to rice plants in rice fields. The results of the assistance show that the farmers understand the knowledge about water hyacinth organic fertilizer, the method of making it and its application to rice plants in the fields. In addition, the application of water hyacinth fertilizer which contains 2 nutrients, namely humic acid and trichoderma mushrooms which are found in stale rice as one of the ingredients in the fertilizer mixture can improve soil structure by breaking down organic substances in the soil thereby contributing to an increase in plant height. , number of tillers/clump, and weight of 1000 seeds compared to rice plants that were not applied water hyacinth organic fertilizer